2017
DOI: 10.3311/ppch.9667
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Delineation of Leachate Plumes

Abstract: Measurement and calculation of the carbon isotopic composition of groundwater from piezometers located around a reclaimed landfill were performed in order to test the method to distinguish the piezometers localized within the contaminated area and to identify the boundaries of the leachate plume. In order to select the best method for delineation of the leachate plume it was analyzed: chemical composition, the stable carbon isotopic composition in groundwater, and the calculation of carbon isotopic composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Such a comparison indicates differences between background water and leachate-contaminated water and hepls to delineate the area of contaminated groundwater. A good solution seems to be to compare the concentration of calcium and bicarbonates concentrations in the groundwater around the landfill [10]. Generally, this relationship indicates the areas not impacted by the landfill contamination.…”
Section: Methods Based On Physicochemical Composition Of the Watermentioning
confidence: 99%
See 2 more Smart Citations
“…Such a comparison indicates differences between background water and leachate-contaminated water and hepls to delineate the area of contaminated groundwater. A good solution seems to be to compare the concentration of calcium and bicarbonates concentrations in the groundwater around the landfill [10]. Generally, this relationship indicates the areas not impacted by the landfill contamination.…”
Section: Methods Based On Physicochemical Composition Of the Watermentioning
confidence: 99%
“…Generally, this relationship indicates the areas not impacted by the landfill contamination. As discussed previously, sometimes this method is not appropriate [10]. Assuming that the landfill leachate contains high concentrations of dissolved organic matter (as a result of organic matter biodegradation), which might contaminate the groundwater, BOD/COD ratio can be used to assess the spread of the leachate plume in the aquifer [21,22].…”
Section: Methods Based On Physicochemical Composition Of the Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Leachate migration in landfills is due to water percolation that accumulates within or below the landfills especially in unsealed landfills above aquifer [10]. A leachate is typically characterized by two factors, viz, its composition and the volume generated [11] both varies among landfills and highly influenced by type of waste, volume, age, climatic conditions, mode of operation and landfilling technology [11], [12]. The efficiency or adequacy of a landfill is in the monitoring of leachate and regular control of groundwater migration [13].…”
Section: A Monitoring Of Landfill Sitesmentioning
confidence: 99%
“…Various methods can be employed to delineate leachate plumes and these were reviewed by Mukherjee et al [5]. Commonly employed methods are: monitoring of groundwater level and water quality tracers in boreholes/wells around the landfill [6,7], isotopic characterization of groundwater in piezometers installed around the landfill [8], geophysical methods [9][10][11], and modelling of transport and biogeochemical processes [12]. Although a large body of literature exists on techniques to determine the composition and delineation of leachate plumes, fewer studies were found that characterize pollution leachates over time [13] and at different groundwater depths [14,15].…”
Section: Introductionmentioning
confidence: 99%